EPILEPSY IN CHILDREN WITH MYTOCHONDRIAL DISEASES: DIAGNOSTICS AND TREATMENT FEATURES - N. N. Zavadenko; A. A. Kholin (Эпилепсия и пароксизмальные состояния)
Mitochondrial diseases (MD) represent a large clinically heterogeneous group of disorders that arise as a result of dysfunction of the mitochondrial respiratory chain. The article discusses clinical features of the MD, accompanying by epilepsy. Two case reports are presented of MELAS syndrome and Alpers-Huttenlocher syndrome. The genetic background of MD is discussed as well as methods for establishing the diagnosis of MD and peculiarities of antiepileptic therapy